2022
DOI: 10.3390/buildings12081115
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Novel Angle Bracket Connection in Cold-Formed Steel Structures

Abstract: In this study, an innovative fabricated angle bracket connection for joining cold-formed steel structures is presented and investigated. The innovation lies in the especially designed and manufactured angle bracket and in the method of connecting the angle bracket for the C-profile using clinch pressing. This novel angle bracket can be used to connect cold-formed steel elements such as beam trusses at the ends of the chords or for anchoring the column base. Five specimens were fabricated and experimentally tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The Partial safety factor 𝛾 𝑀2 was neglected to obtain the characteristic value of the bearing resistance. Both calculation methods used average values of experimentally determined material properties [2]. The 3 mm (𝑡 1 ) thick DX51D steel of the U-connector has an average tensile strength of 414.07 MPa (𝑓 𝑢,1 ), while the 1.15 mm (𝑡 2 ) thick S550 GD steel of the C-profile has an average tensile strength of 704.98 MPa (𝑓 𝑢,2 ).…”
Section: Calculation Of Bearing Resistance Of Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Partial safety factor 𝛾 𝑀2 was neglected to obtain the characteristic value of the bearing resistance. Both calculation methods used average values of experimentally determined material properties [2]. The 3 mm (𝑡 1 ) thick DX51D steel of the U-connector has an average tensile strength of 414.07 MPa (𝑓 𝑢,1 ), while the 1.15 mm (𝑡 2 ) thick S550 GD steel of the C-profile has an average tensile strength of 704.98 MPa (𝑓 𝑢,2 ).…”
Section: Calculation Of Bearing Resistance Of Connectionmentioning
confidence: 99%
“…To achieve continuity of the beam trusses over more spans while keeping the truss beams in between wall panels, a connection with two innovative connectors for the CFS members has been designed (Figure 1). One of these connectors is a novel angle bracket that was introduced in a previous study [2]. It can be used to anchor CFS members and panels and to connect truss ends to steel, concrete, or other common structures.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address this issue and increase the initial elastic stiffness, an optimization of the proposed connection was carried out. Furthermore, an analysis of the angle bracket alone in the previous work showed that its elastic stiffness was about 7.7 kN/mm [19]. The optimization was designed to maximize the use of the angle brackets in the truss beams while minimizing the load-transmitting role of the U-connector and CFS column in the tension and compression components of the connection.…”
Section: Optimisation Of Cfs Connection Under Compression Loadingmentioning
confidence: 99%
“…In order to achieve continuity of the trusses over more spans and at the same time keep the trusses submerged between walls, a connection with two innovative connectors for CFS members has been designed (Figure 1). One of these connectors is a novel angle bracket that was presented in a previous study [19]. It can be used to anchor CFS members and panels and to connect truss ends to CFS columns, concrete, steel or other common structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation